PENGGUNAAN MEDIA KOTAK BAPER (BELAJAR PERKALIAN) BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN PERKALIAN DI KELAS 3 SD NEGERI 3 PASIRIPIS - Ulfah Fauziah; Iis Nurasiah; Luthfi Hamdani Maula (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted with the aim of improving students' multiplication skills using local wisdom-based BAPER box media in grade 3 SD Negeri 3 Pasiripis, Surade, Sukabumi in the 2024/2025 school year. The type of research used is Kemmis and Mc Taggart model of classroom action research which consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 3rd grade students of SD Negeri 3 Pasiripis, totaling 25 students. Data collection techniques used observation and tests. The data that has been collected is then analyzed descriptively and presented in the form of tables and graphs. From the results of the multiplication ability test conducted at the end of each cycle, it is known that the students' multiplication ability has increased every cycle. The average value obtained in the pre-cycle was 56.3 then increased by 11.1 so that in cycle I the average value obtained was 67.4. In cycle II, the average value increased again by 10.2 so that the average value obtained in cycle II was 77.6. In the pre-cycle the classical completeness reached 40% and was included in the criteria less. In cycle I, there was an increase of 24% so that the classical completeness in cycle I was 64% and was included in the sufficient criteria. In cycle II, there was an increase of 32% so that in cycle II the classical completeness was 96% and included in the good criteria. It can be concluded that the use of BAPER box media can improve the multiplication skills of elementary school students.